Mesa Redonda : Incumplimiento Contractual - Beltrán, Jorge (2021)
Jorge Beltran (Perú) - Panelista; Sandra Echaiz (Perú) - Panelista; Leandro García (Perú) - Panelista; Alfredo Soria (Perú) - Moderador